The Effectiveness of Cognitive Behavior Group Counseling with Cognitive Restructuring Techniques to Reduce Stress and Anxiety in Cyberbullying Victims at School - I Made Sonny Gunawan; Ichwanul Mustakim; I Made Gunawan (Grief and Trauma, 2025)
The purpose of this study was to confirm the effectiveness of cognitive-behavioral group counseling with cognitive restructuring techniques in reducing stress and anxiety caused by cyberbullying in students. This study was a true experiment with a two-factorial design. The subjects in this study were 20 students at Senior High School 3 Mataram, Indonesia. Data were collected using the Adaptive Personality Scale from the Acculturative Stress Scale (ASS) and the Social Anxiety Scale (SAS). Data were analyzed using one-way ANOVA statistics. The results of this study indicate that cognitive-behavioral group counseling with cognitive restructuring techniques is effective in reducing stress and anxiety. Furthermore, the results showed that cognitive-behavioral group counseling with restructuring techniques was more effective in reducing anxiety than stress.